Evolution of teaching and evaluation methodologies: the experience in the computer programming course at the universidad nacional de colombia (2014)
In this paper, we present the evolution of a computer-programming course at the Universidad Nacional de Colombia (UNAL). The teaching methodology has evolved from a linear and non-standardized methodology to a flexible, non-linear and student-centered methodology. Our methodology uses an e-learning platform that supports the learning process by offering students and professors custom navigation between the content and material in an interactive way (book chapters, exercises, videos). Moreover, the platform is open access, and approximately 900 students from the university take this course each term. However, our evaluation methodology has evolved from static evaluations based on paper tests to an online process based on computer adaptive testing (CAT) that chooses the questions to ask a student and assigns the student a grade according to the student’s ability.